Current scenario, challenges and way forward for augmenting tobacco control policies and programs in India: a community-based qualitative study - Muralidhar M Kulkarni; Manpreet Bains; Veena G Kamath; Shalini Bassi; Monika Arora; Kirthinath Ballala; Rohith Bhagawath; Priyanka Bantwal; Ilze Bogdanovica; John Britton (Global Health Action)
Background Tobacco use has resulted in a staggering number of illnesses and premature deaths worldwide. India has the world’s second-highest level of tobacco consumption. The study aimed to explore the reasons of initiation among adolescents and understand community stakeholders’ perceptions about the current tobacco control policies and challenges faced in implementing it for youth along with future recommendations. Methods Focus Group Discussions (FGDs) were conducted with adolescents in grades 7th–9th, teachers, parents, and police officers, along with in-depth interviews (IDI) with tobacco vendors. These were digitally audio-recorded and transcribed verbatim. Data was analyzed using inductive thematic analysis. Results Twenty-two focus groups were conducted with adolescents, 10 with parents, 10 with teachers (n = 83), 5 with police (n = 42) and 10 tobacco vendors completed one-to-one interviews. Stakeholders identified gaps in tobacco control policy implementation and recommended stricter enforcement. Solutions such as modifying on-screen health warnings, developing novel ways like live demonstration of patients suffering from tobacco use which creates awareness about tobacco harms, countering tobacco industry marketing strategies, restricting tobacco product sales, lowering affordability, and prominently displaying tobacco-free film rules were recommended. Conclusion The study provides a thorough understanding of factors that lead to tobacco initiation and stakeholder’s opinion on youth-related tobacco legislation that provides direction for strengthening existing tobacco control efforts. There is a need for novel ways to educate the child’s microenvironment, specifically in school and family environment. The findings also emphasize the importance of multi-sector involvement and better enforcement of tobacco control laws.